Modelos de crecimiento diamétrico para Nothofagus obliqua = Diameter growth models for Nothofagus obliqua - Chauchard, Luis Mario; Sbrancia, Renato (Facultad de Ciencias Forestales y Recursos Naturales, Universidad Austral de Chile, 2023)
Non-linear, Bertalanffy-Richards-type models of diameter growth were developed for Nothofagus obliqua and fitted for different social tree strata using the diameter annual increment (id) and diameter at breast height (dap). The biological and statistical analyses were conducted from two different sources; an independent data set taken mainly from permanent sample plots and a real growth series obtained from tree cores and stem analyses. Models for different purposes were obtained through both data sets. For the prediction of short-term diameter increments, a model was obtained that related independent data of trees belonging to the same social stratum. Models of higher biological meaning were obtained by relating the growth series and their significance and are discussed here. By means of these biological models, the growth dynamics of N. obliqua were analyzed under different competitive status.